Community Gardening as a Way to Build Cross-Cultural Community Resilience in Intersectionally Diverse Gardeners: Community-Based Participatory Research and Campus-Community-Partnered Proposal - Mejia, Angie; Bhattacharya, Manami; Miraglia, Joshua (JMIR Research Protocols, 2020)
BackgroundCommunity-based agriculture has been found to decrease food insecurity and alleviate health inequities. Furthermore, it provides a sense of ownership, resources to help integrate new communities, and a space to nurture existing cultural identities for intersectionally diverse gardeners. This sense of belonging in connection with access to growing plots has been linked to psychological well-being and resilience. However, little is known about how the psychosocial benefits of plot ownership affect resilience and which aspects of this resilience are salient. ObjectiveThis community-based participatory research (CBPR) project will examine the role of community gardens in decreasing food insecurity and facilitating various forms of resilience in food-insecure groups in Rochester, Minnesota. Since participation in community gardens nurtures various forms of resilience along individual, group, and community dimensions, our research seeks to understand how dimensions of resilience vary along intersectional lines. In addition to mapping the psychosocial benefits linked to plot ownership, we find that examining which forms of resilience are fostered in community-based agricultural projects addresses an important gap in the academic literature. This can help us propose policy-level practices that reduce health inequities connected to food and nutrition at the local level. MethodsUsing a mixed methods approach, this ongoing community-campus partnership will examine the experiences of current and new plot owners. As a CBPR project, our data collection plan, from design to dissemination, incorporates the intellectual and creative labor of the individuals representing members of the campus community (ie, college students and faculty members engaged in other citizen science projects hosted by the garden), community growers, individuals involved in the community garden’s board, and representatives of various organizational bodies. Data collection activities will consist of surveys, in-depth interviews, and photovoice. ResultsThis project was funded in January 2020 and approved by the University of Minnesota's Institutional Review Board in March 2020. For the 2020 growing season, we will conduct evaluative interviews about the effect of COVID-19 on community gardeners, including their experiences during this growing season. For the 2021 growing season, data collection, via pre- and postsurveys, is projected to begin in March 2021 and end in November 2021. We will also conduct in-depth interviews from January to April 2021. Data analysis will commence in April 2021. Photovoice activities (ie, data collection, analysis, synthesis, and dissemination) are expected to take place during the spring and summer of 2021. ConclusionsFindings emerging from this study will provide the preliminary data to foreground community gardening projects and initiatives to improve physical and mental health outcomes in food-insecure communities. Also, the data collected will highlight the role of CBPR methods in disseminating information about the organizational practices of the community garden; this will assist others in planning and implementing similar projects. International Registered Report Identifier (IRRID)PRR1-10.2196/21218